Afscheid van Troelstra in de Haagse Dierentuin. Plaats van personen aangegeven onder foto. Uit: Het Leven, 26-9-1925
Afscheid van Troelstra in de Haagse Dierentuin. Plaats van personen aangegeven onder foto. Uit: Het Leven, 26-9-1925.